Using Social Media Analysis to Improve E-commerce Marketing Strategies - Semenda, Olha; Sokolova, Yuliia; Korovina, Olena; Bratko, Oleksandra; Polishchuk, Iryna (International Review of Management and Marketing, 2024)
This study investigates the application of game theory and matrix-based analysis in enhancing social media marketing strategies for e-commerce businesses. By integrating these mathematical models with social media analytics, aim to provide a comprehensive framework that can predict consumer behavior, optimize competitive strategies, and improve engagement on digital platforms. This study’s application of a game theory matrix model on social media marketing strategies showcased clear benefits for e-commerce entities, with aggressive marketing tactics boosting market share by 30% against passive competitors and achieving a 20% increase even when competitors also adopted aggressive approaches. The Nash Equilibrium emphasize the balanced market share gains when both firms engaged in aggressive strategies. Statistical analysis reinforced the efficacy of these strategies, with a chi-square test yielding a significant value of 13.4, suggesting a strong link between aggressive marketing and enhanced engagement metrics. Regression analysis further validated the impact of engagement on sales, indicating that a 1% increase in likes, comments, and shares corresponded to a 0.75% uplift in sales, evidenced by significant predictors with β values of 0.25, 0.35, and 0.40 for likes, comments, and shares respectively. Content analysis and consumer surveys highlighted a preference for authentic, value-aligned content, with aggressive strategies leading to a 50% higher engagement rate and a 60% consumer preference for such content, emphasizing the critical role of strategic alignment with consumer expectations. Incorporating game theory and matrix-based analysis into e-commerce social media strategies offers a novel approach to understanding and leveraging the complex interplay of consumer interactions and competitive dynamics. This methodology enables marketers to devise more targeted, adaptive, and effective marketing campaigns, driving growth and enhancing consumer satisfaction in the competitive digital marketplace.